2022
DOI: 10.3390/molecules27217479
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Values and Potential Risks Evaluation of Ginkgo biloba Leaf Extract (GBE) Drinks Made from the Leaves in Autumn as Dietary Supplements

Abstract: Ginkgo tea and ginkgo wine are two familiar Ginkgo biloba leaf extract (GBE) drinks in the form of dietary supplements (DS) used for healthcare in east Asia. Nevertheless, a comprehensive evaluation of their safety and efficacy is still lacking. In this study, GBE drinks were prepared from naturally newly senescent yellow leaves (YL) and green leaves (GL) in autumn. Their total flavonoids, antioxidant capacity and prescribed ingredients were investigated. In brief, the proportions of total flavonoids, total fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Further analysis showed that the flavonoid profiles in the isolated fungi were quite different from those in the ginkgo leaves (Figure S6B). Flavonol glycosides in the ginkgo leaves were mostly distributed within the retention time points of 8-20 min in our analysis, which were the major parts of the medicinal composition of standard ginkgo leaf extract [37]. However, the flavonoid compounds in the endophytic fungi were mainly distributed in the time points from 15 to 40 min (Figure S6B).…”
Section: Metabolite Analysis Of Endophytic Fungi and Their Effects On...mentioning
confidence: 70%
See 1 more Smart Citation
“…Further analysis showed that the flavonoid profiles in the isolated fungi were quite different from those in the ginkgo leaves (Figure S6B). Flavonol glycosides in the ginkgo leaves were mostly distributed within the retention time points of 8-20 min in our analysis, which were the major parts of the medicinal composition of standard ginkgo leaf extract [37]. However, the flavonoid compounds in the endophytic fungi were mainly distributed in the time points from 15 to 40 min (Figure S6B).…”
Section: Metabolite Analysis Of Endophytic Fungi and Their Effects On...mentioning
confidence: 70%
“…Quercetin was used to draw the standard curve. Profiles of flavonol glycosides, flavonol aglycones, and biflavones were analyzed using HPLC-MS/MS as described by Su et al [37].…”
Section: Total Flavonoid Determination and Metabolite Analysismentioning
confidence: 99%